Utilisation of nano materials in enhancing strength and durability properties of ultra high performance concrete (UHPC) / Muhd Norhasri Muhd Sidek - Muhd Sidek, Muhd Norhasri (Institute of Graduate Studies, UiTM, 2017)
Hydration gel (C-S-H) is major component in binding of concrete and refining of the C-S-H gel is difficult to be done by using micro based materials. For this research, inclusion of nano materials in UHPC is expected to overcome the problem by providing ultra filler effect. In this study, the utilisation of nano material in UHPC was done by using additive or replacement method for cement and UHPC mix and generated based on a series of trial modified mixes originally formulated by previous researchers. For this research, two types of nano materials were selected. Firstly, nano kaolin samples were prepared from kaolin using milling and then underwent calcination process to produce nano metakaolin. Secondly, nano clay was provided by Sigma (M) and underwent calcination process to convert to nano metaclay. Characterisation of cementitious materials were confirmed by its particle size, chemical composition and morphology properties and evaluated using Laser particle Analyser, X-Ray Fluorescence (XRF), X-Ray Diffraction (XRD) and Scanning Electron Microscope (SEM). UHPC mixes were developed by incorporating nano materials with (addition) and without (replacement) addition of metakaolin. The inclusion of nano materials as an additive and cement replacement material (without metakaolin) based on percentage of increment from 1, 3, 5, 7 and 9 %...